VIDEO PROFIL SEBAGAI MEDIA PROMOSI DIGITAL SD MUHAMMADIYAH 1 CANDI LABSCHOOL UMSIDA - Asmaul Khusna Tri Wulan Juli; Rayhan Rizq Iskandar; Moch. Nur Faizin; Ainur Rochmaniah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of digital technology encourages educational institutions to optimize visual-based promotional media in building the image of the institution and reaching the wider community. SD Muhammadiyah 1 Candi Labschool UMSIDA (SD Mica) has used social media as a means of information, but it does not have a conceptual promotional media to display the school's identity in its entirety. Therefore, this community service activity aims to strengthen the school's digital promotion through the creation of profile videos that represent the vision and mision, superior programs, facilities, and inclusion education system. The implementation method includes the stages of video production consisting of pre-production, production, and post-production. The results of the service activities are in the form of school profile videos that are ready to be published through digital media and used as a means of promotion, especially in new student admission activities.